KORELASI MINAT ANIME TERHADAP KEMAMPUAN GRAMATIKA MAHASISWA PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU (STUDI KASUS PERNYATAAN SETUJU DAN TIDAK SETUJU) - Dwine Nur Swetira; Hermandra Hermandra; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
ABSTRACT Anime is a typical Japanese animation that has many fans around the world, including in Indonesia. Many Japanese learners are interested in learning Japanese because they were previously fond of anime. This also happened to students at the Riau University Japanese Language Education Study Program. This study aims to see the correlation between the hobby of watching anime and students' Japanese language skills. This study is limited to statements expressing agreement and disagreement in Japanese. The method used in this research is quantitative method. The instruments used were questionnaires and tests. The results of the analysis show that there is a positive correlation between interest in anime and grammatical competence, namely in expressing opinions, which is 5.3%.Key Words: anime, correlation, grammar skil